Comparison of the Three Phase Bone Scintigraphy and Tc-99m Ciprofloxacin Scintigraphy in Diagnosis of Septic and Aseptic Loosening of the Hip and Knee Prosthesis - Karyağar, Sevda Sağlampinar; Karyağar, Savaş; Uslu, Rabia; Mülazımoğlu, Mehmet; Özpaçacı, Tevfik; Uyanık, Ercan (Fırat University, 2013)
Objective: In this study, the results of three phase bone scintigraphy and Tc-99m ciprofloxacin scintigraphy were assessed comparatively in the diagnosis of the septic and aseptic loosening of the hip and knee prosthesis. Materials and Methods: Fifty patients who were referred to our clinic with the pre-diagnosis of infection were included in the study. Thirty two of the patients (64%) had hip prosthesis and 18 (36%) had knee prosthesis. Three phase bone scintigraphy and Tc-99m ciprofloxacin scintigraphy were applied at least 3-5 days interval in our clinic. Results: Three phase bone scintigraphy was reported as positive for 23 patients (46%) and negative for 27 patients (54%) in terms of infection. Tc-99m ciprofloxacin scintigraphy was reported as positive for 19 (54%) and negative for 31 patients (62%). The sensitivity for the three phase bone scintigraphy was found to be 100%. It was 86.6% for the Tc-99m ciprofloxacin scintigraphy. Specificity was 77.5% versus 82.8% (p0,05); negative predictive value was 100% versus 93.5% (p0,05), respectively. Conclusion: Besides being a sensitive method, three phase bone scintigraphy can be used confidently in preventing from the infection existence. Since, the specifity of Tc-99m ciprofloxacin scintigraphy is higher when compared with the three phase bone scintigraphy; the usage of both method in the septic-aseptic loosening sorting is suitable.

Amaç: Bu çalışmada kalça ve diz protezlerindeki septik-aseptik gevşeme ayırıcı tanısında üç fazlı kemik sintigrafisi ve Tc-99m siprofloksasin sintigrafisinin sonuçları karşılaştırmalı olarak değerlendirildi. Gereç ve Yöntem: Çalışmaya enfeksiyon ön tanısıyla kliniğimize yönlendirilen 50 hasta dahil edildi. Hastaların 32'sinde (% 64) kalça protezi, 18'inde (% 36) diz protezi mevcuttu. Hastalara en az 3-5 gün arayla üç fazlı kemik sintigrafisi ve Tc-99m siprofloksasin sintigrafisi çekildi. Bulgular: Üç fazlı kemik sintigrafisi, 23 (% 46) hastada enfeksiyon açısından pozitif, 27 (% 54) hastada ise enfeksiyon açısından negatif olarak rapor edildi. Tc99m siprofloksasin sintigrafisi; 19 (% 38) hastada pozitif, 31 (% 62) hastada negatif olarak rapor edildi. Üç fazlı kemik sintigrafisi için sensitivite % 100 iken Tc-99m siprofloksasin sintigrafisi için % 86.6 (p0.05); negatif prediktif değer % 100'e % 93.5 (p
Kalça Ve Diz Protezlerindeki Septik ve Aseptik Gevşeme Tanısında Üç Fazlı Kemik Sintigrafisi ve Tc-99m Siprofloksasin Sintigrafisinin Karşılaştırılması